2, 2′‐Anhydro‐1‐(3′, 5′‐di‐O‐acetyl‐β‐D‐arabinofuranosyl)uracil, a cyclouridine nucleoside with a C4′‐endo furanosyl conformation. (13th February 2013) - Fu, Ying; He, Yin‐Xia; Hou, Hong‐Xia; Zhu, Wen‐Bo; Li, Hu‐Lin; Wu, Chao; Xian, Fang‐Yan
<x xml:space="preserve">Abstract</x> 2, 2′‐Anhydro‐1‐(3′, 5′‐di‐O‐acetyl‐β‐D‐arabinofuranosyl)uracil, C13H14N2O7, was obtained by refluxing 2′, 3′‐O‐(methoxymethylene)uridine in acetic anhydride. The structure exhibits a nearly perfect C4′‐endo (4E) conformation. The best four‐atom plane of the five‐membered furanose ring is O—C—C—C, involving the C atoms of the fused five‐membered oxazolidine ring, and the torsion angle is only −0.4 (2)°. The oxazolidine ring is essentially coplanar with the six‐membered uracil ring [r.m.s. deviation = 0.012 (5) Å and dihedral angle = −3.2 (3)°]. The conformation at the exocyclic C—C bond is gauche–trans which is stabilized by various C—H...π and C—O...π interactions.